Negative trend in total solar irradiance over the satellite era - Ted Amdur; Peter Huybers (Proceedings of the National Academy of Sciences, 2025)
Linear trends in total solar irradiance (TSI) between different reconstructions of the satellite era, defined as 1978 to 2023, disagree by up to 0.17 W/m 2 per decade. Furthermore, high-quality satellite radiometer observations of the most recent solar cycle, 24, systematically differ from estimates that rely on TSI proxies for reasons that have been unclear. Using a Bayesian Kalman filtering approach to estimate TSI from both satellite-based observations and proxies gives two complementary explanations: recent satellite-based observations of TSI contain unaccounted-for positive linear drifts, and regression-based reconstructions are affected by commonly used solar magnetic proxies becoming less sensitive to TSI variations at low values. After accounting for satellite instrument drifts and reduced sensitivity, direct and proxy observations come into agreement and together indicate a linear trend in overall TSI of −0.15 W/m 2 per decade with a 95% CI of −0.17 to −0.13 W/m 2 per decade between 1980 and 2023.